Case report: A novel case of paraneoplastic voltage gated calcium channel antibodies secondary to appendiceal adenocarcinoma - Patel, Ghanshyam; Sakiri, Ahmet; Brown, Abby; Pasha, Arfa; Bansal, Vibhav (Frontiers in Neurology, 2024)
Voltage gated calcium channels (VGCCs) play a critical role in neural transmission.Antibodies that target these ion channels can disrupt cellular signal transmission resulting in various clinical presentations. VGCC antibodies are most commonly associated with paraneoplastic syndromes such as Lambert-Eatons myasthenic syndrome. Here, we report a 47-year-old female with Stage IV appendiceal adenocarcinoma status post appendectomy and right hemicolectomy, who presented with progressive memory impairment, aphasia, ataxia, weakness, and headache.Neurologic exam was notable for right-sided parietal drift, decreased right arm swing, and ataxia of the bilateral upper extremities, more prominent on the right side. MRI of the brain with and without contrast was unremarkable. Cerebrospinal fluid (CSF) was notable for an elevated myelin basic protein (4.9 ng/mL, normal reference 0.0-3.7 ng/mL) with normal cell count, flow cytometry, and cytology. An extensive serum autoimmune neurology antibody evaluation revealed elevated VGCC autoantibodies (observed value: 96.1 pmol/L, normal range 0.0-30.0 pmol/L). A diagnosis of paraneoplastic voltage gated calcium channel antibodies secondary to appendiceal adenocarcinoma was made. The patient was treated with five exchanges with plasmapheresis over 10 days with significant clinical improvement in her symptoms.